Evaluating the in vitro anti-metastatic effects of silver(I) phosphine complexes on malignant breast cancer cell lines - Ferreira, Mizan (University of the Witwatersrand, Johannesburg, 2023)
Breast cancer is the most diagnosed cancer type among females worldwide. Metastasis, the spread of cancer cells from the primary tumour and establishment of macroscopic secondary tumours, is regarded as the most dangerous characteristic of cancer cells as it is responsible for over 90% of cancer-related deaths. Globally there is a lack of drugs available to specifically target or prevent either the dissemination of cells from the primary tumour or the establishment of distant metastases. The purpose of this study was to ascertain whether a series of silver(I) phosphine complexes, which have previously been shown to display anti-cancer properties in vitro, are also effective as anti-metastatic compounds. The migration, invasion and adhesive abilities of two malignant breast cancer cell lines, MCF-7 and MDA-MB-231, in response to silver(I) phosphine treatment were evaluated. In addition, the colony-forming abilities of cells under both anchorage-dependent and -independent conditions were investigated. Furthermore, the effects of silver(I) phosphine treatment on the expression and activities of key metastatic proteins, matrix metalloproteinases (MMPs), were studied. Of the nine complexes evaluated, all of them showed the ability to reduce one or more metastatic steps namely cell migration, invasion through collagen towards a chemoattractant or adhesion to collagen. In addition, a selected number of complexes reduced the colony-forming abilities of MCF-7 and/or MDA-MB-231 cells in culture plates as well as in soft agar. Moreover, three of these complexes increased the in vitro invasion and colony formation of breast cancer cells. Further investigation into complexes showing anti-metastatic abilities revealed that, apart from one complex on MDA-MB-231 cells, anti-metastatic effects were not achieved through a reduction in MMP levels or activities. The findings presented here show the potential for silver(I) phosphine complexes to reduce the in vitro metastatic abilities of breast cancer cells, warranting further investigations into these complexes for their use as anti-metastatic drugs.
A thesis submitted in fulfilment of the requirements for the degree Doctor of Philosophy, to the Faculty of Science, School of Molecular and Cell Biology, University of the Witwatersrand, Johannesburg, 2023.
Keywords: Breast cancer; Anti-metastatic effects; Silver(I) phosphine complexes; UCTD; SDG-3: Good health and well-being